(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
In the last twenty years the city has progressively dispersed in a vast territory, becoming a city with very low densities incompatible with the urban dimension. The city went on its own, both spontaneously, with the abusive, but also when it was “planned”. For example, it was decided to distribute alleged centralities that would never have been served by an efficient public transport service. What city has Rome become? A city that has experienced a dispersed expansion and has produced settlements in which more and more residents are attracted. Now, around the ring road, immediately before and immediately afterwards, one million Roman citizens live, if not more. Almost a third of the population lives there.